Lipase production by solid-state fermentation of olive pomace in tray-type and pressurized bioreactors - Oliveira, Felisbela (2018)
Background: Bioreactor type, sterilization and specific operational conditions are key factors for the scale-up of solid-state fermentation (SSF). This work deals with the lipase production by SSF of olive pomace (OP) at a traditional tray-type and pressurized bioreactors. Important aspects for SSF at bioreactors were studied, such as the need of sterilization and moisture content (MC) control. RESULTS At larger scale, there was no significant difference in lipase production between sterilized and unsterilized substrates, but MC control had significant impact. The production of lipase in a pressurized bioreactor, under air absolute pressure of 200 kPa and 400 kPa, was two-fold higher than in tray-type bioreactor using the same amount of substrate (500 g) and the same bed height. The protein content of substrate increased from 10 to 18% (w/w) after SSF and the fermented solid presented an antioxidant activity of 10 mmol Trolox kg-1. CONCLUSIONS SSF in pressurized bioreactor allowed to efficiently produce lipase with higher substrate bed height in contrast to that in tray-type bioreactor. The improvement of nutritional value of substrate by SSF indicates its potential applicability in animal feed.